Modeling Pharmacokinetics/Pharmacodynamics of Abatacept and Disease Progression in Collagen-Induced Arthritic Rats - A Population Approach - Lon, Hoi-Kei (2013)
The PK / PD of abatacept, a selective T-cell co-stimulation modulator, was examined in rats with collagen-induced arthritis (CIA) using a nonlinear mixed effect modeling approach. Male Lewis rats underwent collagen induction to produce rheumatoid arthritis. Two single-dose groups received either 10 mg/kg intravenous (IV) or 20 mg/kg subcutaneous (SC) abatacept, and one multiple-dose group received one 20 mg/kg SC abatacept dose and four additional 10 mg/kg SC doses. Effects on disease progression (DIS) were measured by paw swelling. Plasma concentrations of abatacept were assayed by enzyme-linked immunosorbent assay (ELISA). The PK / PD data were sequentially fitted using NONMEM VI. Goodness-of-fit was assessed by objective functions and visual inspection of diagnostic plots. The PK of abatacept followed a two-compartment model with linear elimination. For SC doses, short-term zero-order absorption was assumed with F = 59.2 %. The disease progression component was an indirect response model with a time-dependent change in paw edema production rate constant (k(in)) that was inhibited by abatacept. Variation in the PK data could be explained by inter-individual variability in clearance (CL) and central compartment volume (V(1)), while the large variability of the PD data may be the result of paw edema production (k(in)(0)) and loss rate constant (k(out)). Abatacept has modest effects on paw swelling in CIA rats. The PK / PD profiles were well described by the proposed model and allowed evaluation of inter-individual variability on drug- and DIS-related parameters.